Market-Farm Linkages and Land Use Change : A Quebec Case Study - Smith, William (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1974)
The paper presents the results of research into the function of farm-market linkages in the evolution of hybrid grain-corn production in Southern Québec. The evolution of the physical structure of the market, the nature of market demand, and the farmers' perception of the market, are all identified as significant variables in the location pattern of grain-corn production. The direct role of the market as an information source is examined and found to influence positively both the rate and direction of change. The use of free seed samples and the establishment of contract marketing further confirm these findings.